In-Situ Scanning Electron Microscope Observations of Strain-Confined Lithium Nucleation at Electrode/Electrolyte Interfaces in All-Solid-State-Lithium Battery. Issue 1754 (10th June 2015) - Motoyama, Munekazu; Ejiri, Makoto; Iriyama, Yasutoshi
ABSTRACT: We have studied electrochemical Li deposition/dissolution processes at amorphous solid electrolyte (LiPON) interfaces with 30-nm-thick-Cu-current collectors at different current densities by in-situ scanning electron microscopy (SEM). When the current density is smaller than 300 μA cm −2, Li islands continue to grow under a Cu film without coalescing with their neighbors. Consequently, they produce small cracks in the Cu film leading to isolated Li rod growth from the cracks. On the other hand, a current density of 1.0 mA cm −2 provokes the nucleation of Li islands with a higher number density. They rapidly coalesce under a Cu film in all lateral directions before cracking the Cu film. High current density conditions therefore suppress Li rod growths.